UJI STABILITAS FISIK SEDIAAN EMULGEL MINYAK ATSIRI PALMAROSA (Cymbopogon martinii) - Andriani, Disa; Puspitasari, Dian (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Topical anti-inflammatory treatment can be administered by formulating Palmarosa essential oil into an emulgel dosage form at concentrations of 2%, 4%, and 6%, which is then tested on rats. In topical preparations, storage conditions greatly affect stability; therefore, stability testing is necessary to determine whether the preparation remains suitable for use. This study aims to evaluate the stability of emulgel formulations containing Palmarosa essential oil. The essential oil was formulated into emulgel preparations at concentrations of 2%, 4%, and 6%. Each of the three formulations underwent physical stability tests, including organoleptic evaluation, spreadability, adhesiveness, pH, and viscosity tests, using the cycling test method for 6 cycles. Based on statistical analysis, all emulgel formulations of Palmarosa essential oil demonstrated good physical stability after the cycling test. Changes in pH, adhesiveness, and spreadability parameters were not statistically significant. Formula 3 was considered the most stable formulation, as changes across all parameters were statistically insignificant and it maintained the most consistent physical characteristics after stability testing.